Cryptocurrency framework - TAN, Pearl Hock-neo (Institutional Knowledge at Singapore Management University, 2021)
An interesting puzzle exists with respect to the accounting treatment of cryptocurrencies. The announcement in October 2020 that PayPal was launching its own cryptocurrency service suggests growing acceptability. However, there is no standard that deals with them specifically. We review the classification appropriateness for cryptocurrencies under IAS 2, IAS 7, IFRS 9, and IAS 38. There is a lack of a consensus on the accounting classification and measurement of cryptocurrencies. A framework is needed to classify cryptocurrencies by underlying attributes and to require the appropriate accounting treatment for each classification.